Habib Rishiq Shihab Hate Speaking on Youtube Social Media: Forensic Linguistic Analysis - Alfian Muhajir; Tadjuddin Maknun; Kamsinah Kamsinah; Firman Saleh (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2022)
This study aims to explain the forms of speech acts included in Habib Rishiq Shihab's hate speech on YouTube social media. The data from this survey is Habib Rishiq Shihab's talk uploaded to YouTube social media, including hate speech. The data source for this research is a video format document uploaded to YouTube social media related to Habib Rishiq Shihab's speech, including hate speech. The method used in this study is a qualitative descriptive method. See Data acquisition techniques and annotations. Data analysis using data analysis method, namely qualitative content analysis method (qualitative content analysis). The results of this study indicate that: Habib Rishiq Shihab's speech on YouTube is declarative and question-based. The form of intra-speech action uses declarative and directive idioms. A speech act is a form of effect that affects the interlocutor. The statement is seen as a form of provocation/incitement that can create feelings of hatred or hostility towards specific individuals or groups based on ethnicity, religion, race, and inter-group (SARA), which can be carried out and is classified as illegal, so that it can be categorized as having committed an unlawful act as referred to in paragraph, which is regulated in the formulation of Article 45A paragraph (2) of the ITE Law and Article 160 of the Criminal Code.